President Indonesia’s Speeches: The Talk Meets Action in Functional Analysis - Risnovita Sari; Ikhwanuddin Nasution; Eddy Setia; Mulyadi Mulyadi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study discusses the experiential function in Jokowi’s speeches. The experiential function deals with the processes found in the speeches. There are six processes in the experiential function such as material, mental, verbal, behavioural, relational, and existential process. The study is aimed to identify the processes and find out the dominant process in the speeches.  The speeches consist of 325 clauses, and the dominant process is material process with 124 clauses or 38,15%, followed by relational process with 79 process or 24,3%, mental process with 51 clauses or 15,7%, existential process 33 clauses or 10,1%, behavioural process 20 clauses or 6,1%, and the least is verbal process 18 clauses or 5,5%. It shows that Jokowi’s speeches are the reflection of his slogan; ‘work, work, and work’.  Jokowi has done a lot of work and he explained it in his speeches.